Understanding sexual and reproductive health need of unmarried adolescents and youth in urban slums: evidence from a formative study in Uttar Pradesh, India - Hitesh Sahni; Mukesh Sharma; Basant Kumar Panda; Emily Das; Samrendra Behera; Neelanjana Pandey; Abhishek Kumar; Kate Graham; Ian Salas (Reproductive Health)
Abstract Background Despite the intentional focus of national programs and strategies in last decade, unmarried adolescents and youth (AY) face multiple challenges related to sexual and reproductive health (SRH) information, and access to health and counseling services. With massive urbanization and growing slum and more focus on married youth, the situation and need of unmarried AY are often overlooked. The present study explores the SRH need of AY to gain a holistic understanding of the SRH landscape in the context of slums of Uttar Pradesh, India. Methods A formative qualitative study was conducted in the slums of two cities in Uttar Pradesh using qualitative research techniques—in-depth interviews (IDI) and focus group discussions (FGDs) with unmarried adolescents and youths aged 15–24 years. Thematic analysis was guided by principles of grounded theory and narrative inquiry, both inductive and deductive approaches. Results The study found limited awareness of SRH issues and often inaccurate knowledge of modern contraceptives among the unmarried youth.Gendered access to SRH information emerged clearly, with boys benefitting from wider peer network, while girls relied on familial networks. Lack of social networks and support, communication gap, and limited reach of health providers have majorly contributed to misinformation and misconceptions. Information through social media and online sources served as a key source of SRH knowledge among adolescents and unmarried youth, but concerns remained about the accuracy and reliability of the information accessed. Structural constraints such as stigma, mobility restrictions, and provider bias further marginalized unmarried youth—especially girls—from accessing reliable SRH services. Conclusion The study highlighted demand for SRH knowledge, source of knowledge, major concerns, and opportunities of AY in urban slums. A clear need for multi-faceted strategies targeting sexual health education, adolescent-responsive SRH services, and expanded digital outreach with verified content for this vulnerable populations are identified. However, targeted intervention through system level approaches for AY can be helpful for dispelling myths and providing accurate information.